Characterization of the Human LPIN1-encoded Phosphatidate Phosphatase Isoforms - Han, Gil-Soo (American Society for Biochemistry and Molecular Biology, 2010)
The human LPIN1 gene encodes the protein lipin 1, which possesses phosphatidate (PA) phosphatase (3-sn-phosphatidate phosphohydrolase; EC 3.1.3.4) activity (Han, G.-S., Wu, W.-I., and Carman, G. M. (2006) J. Biol. Chem. 281, 9210–9218). In this work, we characterized human lipin 1 α, β, and γ isoforms that were expressed in Escherichia coli and purified to near homogeneity. PA phosphatase activities of the α, β, and γ isoforms were dependent on Mg(2+) or Mn(2+) ions at pH 7.5 at 37 °C. The activities were inhibited by concentrations of Mg(2+) and Mn(2+) above their optimums and by Ca(2+), Zn(2+), N-ethylmaleimide, propranolol, and the sphingoid bases sphingosine and sphinganine. The activities were thermally labile at temperatures above 40 °C. The α, β, and γ activities followed saturation kinetics with respect to the molar concentration of PA (K(m) values of 0.35, 0.24, and 0.11 mm, respectively) but followed positive cooperative (Hill number ∼2) kinetics with respect to the surface concentration of PA (K(m) values of 4.2, 4.5, and 4.3 mol %, respectively) in Triton X-100/PA-mixed micelles. The turnover numbers (k(cat)) for the α, β, and γ isoforms were 68.8 ± 3.5, 42.8 ± 2.5, and 5.7 ± 0.2 s(−1), respectively, whereas their energy of activation values were 14.2, 15.5, and 18.5 kcal/mol, respectively. The isoform activities were dependent on PA as a substrate and required at least one unsaturated fatty acyl moiety for maximum activity.